Survival benefit for patients with diffuse intrinsic pontine glioma (DIPG) undergoing re-irradiation at first progression: A matched-cohort analysis on behalf of the SIOP-E-HGG/DIPG working group. (March 2017) - Janssens, Geert O.; Gandola, Lorenza; Bolle, Stephanie; Mandeville, Henry; Ramos-Albiac, Monica; van Beek, Karen; Benghiat, Helen; Hoeben, Bianca; Morales La Madrid, Andres; Kortmann, Rolf-Dieter; Hargrave, Darren; Menten, Johan; et al.
Abstract: Background: Overall survival (OS) of patients with diffuse intrinsic pontine glioma (DIPG) is poor. The purpose of this study is to analyse benefit and toxicity of re-irradiation at first progression. Methods: At first progression, 31 children with DIPG, aged 2–16 years, underwent re-irradiation (dose 19.8–30.0 Gy) alone (n = 16) or combined with systemic therapy (n = 15). At initial presentation, all patients had typical symptoms and characteristic MRI features of DIPG, or biopsy-proven high-grade glioma. An interval of ≥3 months after upfront radiotherapy was required before re-irradiation. Thirty-nine patients fulfilling the same criteria receiving radiotherapy at diagnosis, followed by best supportive care (n = 20) or systemic therapy (n = 19) at progression but no re-irradiation, were eligible for a matched-cohort analysis. Results: Median OS for patients undergoing re-irradiation was 13.7 months. For a similar median progression-free survival after upfront radiotherapy (8.2 versus 7.7 months; P = .58), a significant benefit in median OS (13.7 versus 10.3 months; P = .04) was observed in favour of patients undergoing re-irradiation. Survival benefit of re-irradiation increased with a longer interval between end-of-radiotherapy and first progression (3–6 months: 4.0 versus 2.7; P < .01; 6–12 months: 6.4 versus 3.3; P = .04). Clinical improvement with re-irradiation was observed in 24/31 (77%) patients. No grade 4–5 toxicity was recorded. On multivariable analysis, interval to progression (corrected hazard ratio = .27–.54; P < .01) and re-irradiation (corrected hazard ratio = .18–.22; P < .01) remained prognostic for survival. A risk score (RS), comprising 5 categories, was developed to predict survival from first progression (ROC: .79). Median survival ranges from 1.0 month (RS-1) to 6.7 months (RS-5). Conclusions: The majority of patients with DIPG, responding to upfront radiotherapy, do benefit of re-irradiation with acceptable tolerability. Highlights: Re-irradiation at first progression improves overall survival in patients with DIPG. Symptom improvement after re-irradiation is recorded in 80 % of patients. A model, comprising 5 categories, can predict survival from progression. According to SIOP-E recommendations, re-irradiation at first progression can be considered.